Revealing Conditions of Detailed Water Usage, Daily Life Water Quality, and Awareness Related to Waste Water at Urban Kampung in Indonesia - Toshiyuki Shimizu; Taishi Yazawa; Sri Maryati; Nyimas Suryani; Atsushi Ichiki (Pusbindiklatren Bappenas, 2024)
This research aimed to investigate the actual water use of residents and the quality of well water used daily at the urban kampung located in Bandung, Indonesia. The status of wastewater treatment and residents' awareness of the water environment were also investigated in the target area. The methodology used included a survey of residents, water quality testing, and an assessment of wastewater practices. The results showed that approximately one-half of the respondents used water from the water utility, with the other half using well water as their main domestic water source. Identifying water sources by end-use revealed that residents mainly used bottled water for drinking and cooking. Since Escherichia coli was detected in many wells, it is not recommended that residents drink well water without disinfection. In addition, most of the wastewater in the area was discharged into a nearby river without treatment.